2021
DOI: 10.2106/jbjs.oa.21.00009
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Mortality for Proximal Femoral Fractures Treated at a U.K. Elective Center with a Site-Streaming Policy During the COVID-19 Pandemic

Abstract: Background: COVID-19 led to the reconfiguration of U.K. orthopaedic trauma services because surgical capacity was threatened in acute centers. We report the 30-day mortality of proximal femoral fractures in older adults treated at an elective orthopaedic center. Methods: Patients >60 years old who presented with a proximal femoral fracture to any of 4 sites in the regional trauma network were transferred to our elective center for emergency surgery. Care was modeled accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The majority of patients in these investigations were > 60 years old. The study characteristics and postoperative mortality findings are shown in Table 2 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The most common injury sites were the hip and femur, followed by other lowerlimb sites such as the patella, tibia, ankle, foot, and upper limb.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of patients in these investigations were > 60 years old. The study characteristics and postoperative mortality findings are shown in Table 2 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The most common injury sites were the hip and femur, followed by other lowerlimb sites such as the patella, tibia, ankle, foot, and upper limb.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery within 48 hours of hospital admission does not correlate with a lower mortality rate in COVID-19-positive patients [13]. As shown in Table 3 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], the mean hospital stay length among COVID-19-positive patients undergoing hip and femur surgery was longer than that among COVID-19-negative patients. This result is in line with the study by Kayani et al [37], which stated that hip surgery in COVID-19-positive patients was associated with a longer hospital stay, longer immobilization, more hospitalizations in the intensive care unit, an increased chance of peri-operative complications, and greater mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations